Definition of fibromyalgia severity: findings from a cross-sectional survey of 2339 Italian patients. (13th August 2020) - Salaffi, Fausto; Di Carlo, Marco; Bazzichi, Laura; Atzeni, Fabiola; Govoni, Marcello; Biasi, Giovanni; Di Franco, Manuela; Mozzani, Flavio; Gremese, Elisa; Dagna, Lorenzo; Batticciotto, Alberto; Fischetti, Fabio; et al.
Abstract: Objective: To establish optimal cut-off values for the scores of the revised Fibromyalgia Impact Questionnaire (FIQR), the modified Fibromialgia Assessment Scale (FAS 2019mod), and the Polysymptomatic Distress Scale (PDS) in order to distinguish five levels of FM disease severity. Methods: Consecutive FM patients were evaluated with the three clinimetric indices, and each patient was required to answer the anchor question: 'In general, would you say your health is 1 = very good, 2 = good, 3 = fair, 4 = poor, or 5 = very poor?'—which represented the external criterion. Cut-off points were established through the interquartile reconciliation approach. Results: The study sample consisted of 2181 women (93.2%) and 158 men (6.8%), with a mean age of 51.9 (11.5) years, and mean disease duration was 7.3 (6.9) years. The overall median FIQR, FAS 2019 mod and PDS scores (25th–75th percentiles) were respectively 61.16 (41.16–77.00), 27.00 (19.00–32.00) and 19.0 (13.00–24.00). Reconciliation of the mean 75th and 25th percentiles of adjacent categories defined the severity states for FIQR: 0–23 for remission, 24–40 for mild disease, 41–63 for moderate disease, 64–82 for severe disease and >83 for very severe disease; FAS 2019 mod: 0–12 for remission, 13–20 for mild disease, 21–28 for moderate disease, 29–33 for severe disease and >33 for very severe disease; PDS: 0–5 for remission, 6–15 for mild disease, 16–20 for moderate disease, 21–25 for severe disease and >25 for very severe disease. Conclusions: Disease severity cut-offs can represent an important improvement in interpreting FM.